Noise suppression in pulsed IR thermographic NDT: Efficiency of data processing algorithms; NDT & E International; Vol. 148 - Vavilov V. P. Vladimir Platonovich; Chulkov A. O. Arseniy Olegovich; Shiryaev V. V. Vladimir Vasilyevich; Kuimova M. V. Marina Valerievna; Hai Zhang (2024, 2024)
Title screen